Improving Data Security, Privacy, and Interoperability for the IEEE Biometric Open Protocol Standard - Eduardo Magalhaes De Lacerda Filho; Geraldo P. Pereira Rocha Filho; Rafael Timoteo De Sousa; Vinicius P. Goncalves (IEEE Access, 2022)
Enhancing security, privacy, and interoperability of biometric networks and protocols has been a challenge for many research works for many years. The several proposed approaches still need to integrate these three characteristics while showing security evidence for biometric applications. Therefore, this paper proposes a probabilistic scheme to encrypt biometric database indexes and a novel approach to interoperability among systems interchanging biometric characteristics, thus enhancing the IEEE Biometric Open Protocol Standard (BOPS). We highlight two meaningful improvements in our research when compared to related works. The first one comes from the proposed cryptographic techniques and network schemes. It implies a negligible probability for known attacks to be successful against the proposal, due to its semantic security evidence, as well as the difficulties that it imposes to the attacks, given the high complexity barriers that are unfeasible for the attacker to break in polynomial time, including the modified initialization vector and the nonce for the encryption algorithm. The second improvement comprises the new integrity and control procedures for biometric identification requests that boost the IEEE BOPS’ reliability and contribute to interoperability purposes. The security analysis, proofs, and results demonstrate that the new proposed biometric network is faultless regarding integrity and interoperability while preserving the anonymity of persons whose biometric data is exchanged in the network and stored in the related databases.